Horsehair worms (Nematomorpha: Gordioidea) from Hazarost mountains stream, Kurdstan region, Iraq. - Rahemo, Zohair IF.; Ismail, Honar O.; Mohmmad, Sarbaz I. (Journal of Research in Biology, 2011)
Horsehair worms were recorded for the first time in Hazarost mountains streams, Kurdistan, Iraq. As appeared from its morphological criteria such as cuticular sculpture, measurements, histology of a cross section, it belong to genus: Gordius. It is very difficult to determine the species in the time being but in the light of recent use of sophisticated techniques such as combined large-subunit and small-subunit rRNA gene sequences it will be possible to identify the species